GAMBARAN KEPUASAN DOKTER GIGI DALAM PEMESANAN GIGI TIRUAN DI LABORATORIUM ATHALLAH DENTAL KOTA PEKANBARU - Jihan Natassa; Rheyna Ayuningsih (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2022)
Statisfacation is the perception of something that has met expectations. Based on the initial survey conducted at the Dentist's Practice, which ordered dentures at the Dental Athallah Laboratory, out of 7 dentist respondents who ordered dentures, there were 6 respondents who were dissatisfied with the quality of the product produced, such as the base thickness, and the dentures that were made. loose, 5 respondents felt the service provided was not optimal, 5 respondents felt that the price of denture made from thermos was more expensive than other laboratories, 4 respondents complained about the inappropriate timing. The purpose of this study was to find out a description of the satisfaction of dentists in ordering dentures at Athallah Dental Laboratory Pekanbaru City in 2020. This type of research uses quantitative research which is descriptive in the data collection method using a questionnaire with 29 dentists as respondents. The results of this study indicate that the satisfaction of ordering dentures at the Athallah Dental Laboratory is 15 respondents (51.7%) who are dissatisfied, and 14 respondents who are satisfied (48.3%). The service for ordering dentures at the Dental Athallah Laboratory was not good, there were 10 respondents (34.5%) and 19 respondents (65.5%) felt that the service provided was good. There were 13 respondents (44.8%) who felt that the price for ordering dentures at the Athallah Dental Laboratory was expensive and 16 respondents (55.2%) felt that the price given was cheap. There were 15 respondents (51.7%) who were not on time to order dentures at the Dental Athallah Laboratory and 14 respondents (48.3%) who were not on time. The suggestion from the researchers is to improve the quality of service and the timeliness of dentures.. Bibliography : 34 (2010-2019) Keywords : Satisfaction, Denture, Laboratory